2015
DOI: 10.1097/brs.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Civilian Spinal Gunshot Wounds

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…In our study, roughly two-thirds of patients had neurologic involvement without any patients showing spinal instability. This data is consistent with previous work by Bumpass et al who showed a high rate of neurologic compromise despite low rates of biomechanical instability with CSGSW [ 19 ]. Prior studies suggest that in CSGSW, neural and spinal cord damage are generally due to direct impact, thermal energy, or blast effect ( Figure 4 ) rather than compression or tension as seen in blunt force trauma [ 1 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, roughly two-thirds of patients had neurologic involvement without any patients showing spinal instability. This data is consistent with previous work by Bumpass et al who showed a high rate of neurologic compromise despite low rates of biomechanical instability with CSGSW [ 19 ]. Prior studies suggest that in CSGSW, neural and spinal cord damage are generally due to direct impact, thermal energy, or blast effect ( Figure 4 ) rather than compression or tension as seen in blunt force trauma [ 1 , 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Thoracic region is the most commonly affected area[ 17 ] with most risk of complete injury[ 4 ] for civilian gunshot wounds. In an epidemiological investigation involving combat casualties and including explosions and gunshot injury, Schoenfeld et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent series involving civilians, Bumpass et al . [ 4 ] concluded the surgical indication as post-gunshot spinal infections and persistent CSF leaks. They pointed that injury caused by a small-caliber bullet to the spine infrequently destabilizes the spine, even if all the three columns are impacted.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the civilian literature favors nonsurgical management unless there is evidence of incomplete injury to the spinal cord with progressive neurological deterioration and persistent CSF fistula, migration of bullet within the spinal canal is present. [ 45 ]…”
Section: Role Of Surgerymentioning
confidence: 99%
“…Indications for surgery in his study were spinal infection and persistent CSF leaks. [ 45 ] Yashon et al . also has similar experience in his study of 65 patients of civilian GSW.…”
Section: Role Of Surgerymentioning
confidence: 99%